(untitled) - Carman, Patrick (New York, 2006)
Alexa reveals the origin of the Land of Elyon while defending it against the evil Abaddon and his sinister forces, with not only the last Jocasta at stake but also the nature of the land itself.
Keywords: Fiction; Magic; Fiction; Human-animal communication; Fiction; Voyages and travels